The hydrogen evolution reaction on codeposited Ni-hydrogen storage intermetallic particles in alkaline medium - Bocutti, R.; Saeki, M. J.; Florentino, A. O.; Oliveira, CLF; Angelo, ACD (Elsevier B.V., 2000)
The hydrogen evolution reaction (HER) was studied on Ni-LaNi5 and Ni-MmNi(3.4)Co(0.8)Al(0.8) electrode materials in 1 mol dm(-3) NaOH solution. The steady-state polarization curves and electrochemical impedance spectroscopy experimental data showed a pronounced improvement in HER kinetics when these electrode materials were used. The electrochemical results are in accordance with the Volmer-Heyrovsky mechanism. The kinetic results indicate a more effective improvement in the Heyrovsky step, suggesting an electrocatalytic synergistic effect of the hyper-electronic character of the Ni and the hypo-electronic character of the rare-earth element on the electrode surface. (C) 2000 International Association for Hydrogen Energy. Published by Elsevier B.V. Ltd. All rights reserved.